Sistem Pendukung Keputusan Pemilihan SSD Laptop Menggunakan Kombinasi Metode AHP dan SAW - Wahyu Rahmansyah; Ilka Zufria; M Fakhriza (STMIK Budi Darma, 2023)
The development of computer technology has increased the demand for the right choice in buying an SSD (Solid State Drive) for a laptop. This research is intended to develop a decision support system (DSS) that uses a combination of the AHP (Analytical Hierarchy Process) and SAW (Simple Additive Weighting) methods in selecting laptop SSD at a Medan computer shop. This research consists of several stages. The first stage involves identifying relevant criteria in selecting a laptop SSD, such as price, capacity, speed, durability, and warranty. The AHP method is used to determine the relative weight of each criterion. The second phase involves using the SAW method to assign a value to each criterion and the SSD alternatives available in the store. The suitability score for each alternative is calculated and the system generates recommendations based on the highest score. The decision support system developed in this research is expected to help computer shop owners and customers choose the most suitable laptop SSD according to their needs and preferences. By using a combination of AHP and SAW methods, more objective and accurate results can be obtained in selecting a laptop SSD at a computer shop in Medan. In the context of laptop hardware selection, this research is expected to increase efficiency and customer satisfaction.